A Call for the Application of Patient Safety Culture in Medical Humanitarian Action: A Literature Review. Issue 8 (December 2021) - Biquet, Jean-Marc; Schopper, Doris; Sprumont, Dominique; Michel, Philippe
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aims of the study were to assess lessons learned on patient safety in Organization for Economic Cooperation and Development (OECD) countries and to assess whether they are applied or can be applied to the humanitarian medicine. Methods: This is ( a ) a 2013–2018 rapid literature review of reviews and systematic reviews articles (PubMed database) on "patient safety" and "medical error" to look for lessons learned regarding patient safety in OECD countries and ( b ) a rapid literature review (PubMed and Embase databases) on "humanitarian medicine" and "patient safety, " from their creation to 2018, to find any articles related to patient safety in humanitarian medicine. In both reviews were excluded articles specifically related to one device, disease, or medical act. These reviews were complemented by a Google search. Results: Of the 245 references retrieved, 104 met the inclusion criteria. Of 308 references, 39 respected the inclusion criteria. In OECD countries, patient safety comprises correlated measures taken at three levels. The micro level focuses on individual staff involved in healthcare provision or management; the meso level focuses on medical institutions; the macro level focuses on national healthcare systems. Only one reference mentioned the implementation of a medical error reporting and analysis system in medical humanitarian organization. Conclusions: The adoption of strategies and a culture of safety will need to be adapted to address the variety of intervention contexts and to respond first to the fears and expectations of humanitarian staff. Medical humanitarian organizations, in the absence of an overarching authority for the sector, have a major responsibility in the development of a general patient safety policy applicable in all their operations.